The Human Replicative Helicase, the CMG Complex, as a Target for Anti-cancer Therapy - Seo, Yeon-Soo; Kang, Young-Hoon (Frontiers in Molecular Biosciences, 2018)
DNA helicases unwind or rearrange duplex DNA during replication, recombination and repair. Helicases of many pathogenic organisms such as viruses, bacteria, and protozoa have been studied as potential therapeutic targets to treat infectious diseases, and human DNA helicases as potential targets for anti-cancer therapy. DNA replication machineries perform essential tasks duplicating genome in every cell cycle, and one of the important functions of these machineries are played by DNA helicases. Replicative helicases are usually multi-subunit protein complexes, and the minimal complex active as eukaryotic replicative helicase is composed of eleven subunits, requiring a functional assembly of two subcomplexes and one protein. The hetero-hexameric MCM2-7 helicase is activated by forming a complex with Cdc45 and the hetero-tetrameric GINS complex; the Cdc45-Mcm2-7-GINS (CMG) complex. The CMG complex can be a potential target for a treatment of cancer and the feasibility of this replicative helicase as a therapeutic target has been tested recently. Several different strategies have been implemented and are under active investigations to interfere with helicase activity of the CMG complex. This review focuses on the molecular function of the CMG helicase during DNA replication and its relevance to cancers based on data published in the literature. In addition, current efforts made to identify small molecules inhibiting the CMG helicase to develop anti-cancer therapeutic strategies were summarized, with new perspectives to advance the discovery of the CMG-targeting drugs.